2014
DOI: 10.1021/ed5001697
|View full text |Cite
|
Sign up to set email alerts
|

A Game-Based Approach to an Entire Physical Chemistry Course

Abstract: We designed, implemented, and evaluated a game-based learning approach to increase student motivation and achievement for an undergraduate physical chemistry course. By focusing only on the most important game aspects, the implementation was realized with a production ratio of 1:8 (study load in hours divided by production effort in hours). Student motivation was found to increase significantly: compared to the traditional lecture format, self-study time was estimated to increase more than 3-fold to 4.6 h per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
(74 reference statements)
0
25
0
4
Order By: Relevance
“…Modern gamification efforts use both technology and lower tech (e.g., paper). For example, a quiz-show-style game for increasing lexical communication and a quiz-based approach to learning structure and reactivity of organic compounds; an app for introductory organic chemistry topics; a gamification to bridge precollege and undergrads; a gamification of the entire physical chemistry curriculum; games centered around the periodic table or periodic trends; a European-style board game for organic chemistry; a card game for learning organic chemical transformations and synthesis; a picture game for laboratory items; a green chemistry game for safer design concepts for undergrads and high school students; and an approach that uses a dominos-like game to learn relationships between valence, atomic number, and symbol . Another popular approach uses the Escape Room concept.…”
mentioning
confidence: 99%
“…Modern gamification efforts use both technology and lower tech (e.g., paper). For example, a quiz-show-style game for increasing lexical communication and a quiz-based approach to learning structure and reactivity of organic compounds; an app for introductory organic chemistry topics; a gamification to bridge precollege and undergrads; a gamification of the entire physical chemistry curriculum; games centered around the periodic table or periodic trends; a European-style board game for organic chemistry; a card game for learning organic chemical transformations and synthesis; a picture game for laboratory items; a green chemistry game for safer design concepts for undergrads and high school students; and an approach that uses a dominos-like game to learn relationships between valence, atomic number, and symbol . Another popular approach uses the Escape Room concept.…”
mentioning
confidence: 99%
“…This game also was found to increase self-study time per week among the students. The failure rate in the final examination was also reduced, mainly because of bonus points that students could receive upon successful participation in the game ( Daubenfeld and Zenker, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of research conducted on the effect of digitalbased gamification using experimental design, Tsai and Tsai (2020) found that students across all educational levels all significantly benefit from game-based science learning. Many recent empirical studies have been done in evaluate the effect of digital game-based learning on learning outcomes across academic subjects such as mathematics (e.g., Deng et al, 2020), physics (Wu et al, 2020), chemistry (Daubenfeld & Zenker 2014) and language learning (e.g., Yang, Lin and Chen 2017). Many of such studies shows that students in the gamification group showed increased attention, positive emotion, or learning motivation compared with the control group, although its effect on academic achievement remains to be debated (Ke et al, 2015).…”
Section: Studies Of Gamification In Educationmentioning
confidence: 99%